ADAB MURID TERHADAP GURU MENURUT IMAM NAWAWI DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALIM - Husni, Muhammad; Ardani, Ardani (ADDABANA: Jurnal Pendidikan Agama Islam, 2023)
Abstract: Etiquette holds great significance and demands careful consideration. In his work, "Adab Al-'Alim Wal Muta'alim Wa Adab al-Mufti wa al-Mustafti," Imam Nawawi endeavors to provide insights into "Guidelines for Emphasizing the Importance of Knowledge, Teaching Etiquette, and Learning." This research employs a qualitative library research approach, focusing on the examination of students' conduct towards their educators as per Imam Nawawi's teachings in the book "Adabul 'Alim Wal Muta'alim." The research question at hand is: "What constitutes proper student-teacher etiquette according to Imam Nawawi in 'Adabul 'Alim Wal Muta'alim'?" Meanwhile, the primary aim of this study is to ascertain the code of conduct expected of students towards their teachers based on Imam Nawawi's principles outlined in 'Adabul 'Alim Wal Muta'alim.' Data collection involves the library research method, which entails collecting information indirectly from various sources such as books, journals, magazines, pamphlets, and other pertinent documentary materials. Qualitative descriptive analysis serves as the method for data analysis. The study's findings reveal that Imam Nawawi's guidelines for student-teacher etiquette, as presented in 'Adabul 'Alim Wal Muta'alim,' encompass the following key points: First, humility; Second, the careful selection of a teacher; Third, the utmost respect for teachers; Fourth, the importance of teacher approval and blessings.  Keywords: Adab, Students, Teachers, and The Book of Adabul 'Alim Wal Muta'alim. Abstrak: Adab merupakan sesuatu yang sangat penting dan mesti diperhatikan. Dalam kitab Adab Al-‘Alim Wal Muta’alim Wa  Adab al-Mufti wa al-Mustafti Karya Imam Nawawi, beliau mencoba untuk memberikan gambaran tentang “Butiran-Butiran Nasihat Mengenai Pentingnya Ilmu, Adab Mengajar dan Belajar”. Penelitian ini merupakan penelitian kepustakaan (library research) yang bersifat kualitatif. Penelitian ini mengkaji tentang adab murid terhadap guru menurut Imam Nawawi dalam Kitab Adabul ‘Alim Wal Muta’alim. Adapun rumusan masalah dalam penelitian ini adalah bagaimanaadab murid terhadap guru menurut Imam Nawawi Dalam Kitab Adabul ‘Alim Wal Muta’alim?. Sedangkan tujuan penelitian ini adalah untuk mengetahui adab murid terhadap guru menurut Imam Nawawi Dalam Kitab Adabul ‘Alim Wal Muta’alim. Teknik pengumpulan data menggunakan metode studi pustaka (library research) yaitu berupa teknik pengumpulan data yang tidak langsung ditujukan pada subjek penelitian, melainkan melalui beberapa buku, majalah, jurnal, pamphlet, dan bahan-bahan dokumenter lainnya yang relevan dalam penelitian tersebut. Teknik analisis data menggunakan diskriftif kualitatif. Hasil penelitian menunjukan bahwa adab murid terhadap guru menurut Imam Nawawi dalam Kitab Adabul ‘Alim Wal Muta’alim, yaitu; Pertama; Bersifat Tawadhu. Kedua; Memilih guru. Ketiga; Menghormati guru. Keempat; Ridho guru. Kata Kunci: Adab, Guru, Kitab Adabul ‘Alim Wal Muta’alim, dan Murid.